Arylamino-thieno-oxobutanamides under Lawesson’s conditions : competition between thienylpyrrole and bithiophene formation - Raposo, M. Manuela M. (2005)
1-Aryl-2-thienyl-substituted pyrroles and/or 5-arylamino-2,2´-bithiophenes were synthesized by treatment of arylaminothieno-oxobutanamides with Lawesson’s reagent. These in turn were prepared by direct amidation of 4-oxo-(2-thienyl)butanoic acid through DCC–BtOH mediated reactions.